Addressing Opportunity in Wisconsin's Four-Year Universities: A Comparative Analysis of State College Access Programs - Good, Annalee; Stransky Vaade, Elizabeth (My University, 2009)
This brief explores three examples of state policies designed to help students and families cope with rising tuition costs at four-year institutions: the Wisconsin Covenant, the Georgia HOPE Scholarship Program, and the Indiana Twenty-first Century Scholars Program. The authors evaluate the Covenant, a relatively new state program, in comparison to Twenty-first Century Scholars and HOPE -- two of the first and longest-standing state scholarship programs focused on access to higher education -- in terms of efficiency, equity, and political feasibility. The authors recommend that the state of Wisconsin adopt a hybrid model -- one that integrates components of the existing Wisconsin Covenant with state scholarships targeted to low-income students -- in order to provide students, families, the higher education system, and the state with the highest levels of efficiency and equity.
Keywords: State College Access Programs; Access, Persistence, and Success